Management : challenges for tomorrow's leaders - Lewis, Pamela S.; Goodman, Stephen H.; Fandt, Patricia M. (Mason, Ohio : Thomson/South-Western, 2004)
[This] text addresses the basic concepts of management, the roles of the manager, and the changing nature of both the contemporary organization and the contemporary manager. [The text] explores the managerial function of planning. [It] focuses on the organizing function of management. [It] explores the managerial function of leadership. [It also] examines the management function of control. The foundational principles of control are addressed, and specific attention is given to productivity, quality control, and information systems control. Control is principal tool for achieving quality in the products, services, and processes of the organization, as well as a tool for developing a competitive advantage based on enhanced productivity, increased efficiency, and superior quality.-Pref.
The text's support web site includes downloadable supplements for instructors and powerpoint, interactive practice quizzes, exercises, and other information for students.
Includes bibliographical references (p. 607-639) and indexes.
Keywords: Management